Ordinary people in extraordinary times : the citizenry and the breakdown of democracy - Bermeo, Nancy Gina, 1951- (Princeton University Press, 2003)
Based on extensive research, this book overturns the common wisdom. It shows that the German experience was exceptional, that people's affinity for particular political positions are surprisingly stable, and that what is often labeled polarization is the result not of vote switching but of such factors as expansion of the franchise, elite defections, and the mobilization of new voters. Democratic collapses are caused less by changes in popular preferences than by the actions of political elites who polarize themselves and mistake the actions of a few for the preferences of the many. These conclusions are drawn from the study of twenty cases, including every democracy that collapsed in the aftermath of the Russian Revolution in interwar Europe, every South American democracy that fell to the Right after the Cuban Revolution, and three democracies that avoided breakdown despite serious economic and political challenges.